Aflatoxines: Attention, danger de mort ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Les aflatoxines sont produites par des moisissures ou champignons, en particulier Aspergillus Flavus.